EMBEDDING AHLUSSUNNAH WAL JAMAAH IN MADRASAH MAARIF: INSIGHTS FROM A CASE STUDY - Zakaria, Bahrudin Nur Aziz; Amrullah, Abdul Malik Karim; Mustikawan, Alfin; Anggarini, Ida Fitri (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study explores how the principles of Ahlussunnah Wal Jamaah (Aswaja) are embedded as core values within the educational framework of Madrasah Ma’arif. Aswaja, representing the mainstream Sunni tradition, serves as a foundational ideology in many traditional Islamic educational institutions in Indonesia. Method: Through a qualitative case study approach using a naturalistic research method, this research investigates the strategies used by educators, the integration of Aswaja values in the curriculum, and the influence of institutional culture in promoting religious moderation, tolerance, and balanced Islamic thought. Data were collected through interviews with teachers in one private madrasah in Malang, classroom observations, and document analysis. Result: The findings reveal that Madrasah Ma’arif instills Aswaja principles not only through formal religious instruction but also via character education, extracurricular activities, and school governance. Conclusion: The study concludes that embedding Aswaja values strengthens students’ religious identity while promoting a peaceful and inclusive interpretation of Islam, aligning with the broader goals of national education and social harmony.